(untitled) (Scientific journal of the Fergana State University, 2026)
In the article, the theoretical and methodological foundations of strengthening the sense of national heroism of the Uzbek people in the moral education of young people, the historical and philosophical aspects of strengthening the sense of national heroism of the Uzbek people in the moral education of young people, the priority tasks of strengthening the sense of national heroism in the moral education of young people in the future studied. Also, the concept of moral education and its content are analyzed.